2002
DOI: 10.1007/s00520-002-0397-5
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and hydration for terminal cancer patients in Taiwan

Abstract: Many medical professionals are still confused when facing the reduction of food or fluid intake in terminal cancer patients. The aim of this study was to assess the frequency and causes of the inability of eating or drinking in terminal cancer patients and to investigate the use of artificial nutrition and hydration (ANH); the frequency, type, and the extent to which staff found ANH to be ethically justified. Three hundred forty-four consecutive patients with terminal cancer admitted to a palliative care unit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 21 publications
(25 reference statements)
3
33
0
5
Order By: Relevance
“…This trend of intravenous nutrition/hydration is similar to that reported in Taiwan [21,22]. However, in Taiwan, the proportion of intravenous nutrition was 57% on admission, 46.9% at 1 week, and 53.1% 2 days before death.…”
Section: Discussionsupporting
confidence: 87%
“…This trend of intravenous nutrition/hydration is similar to that reported in Taiwan [21,22]. However, in Taiwan, the proportion of intravenous nutrition was 57% on admission, 46.9% at 1 week, and 53.1% 2 days before death.…”
Section: Discussionsupporting
confidence: 87%
“…Taiwanese families believe that "requesting nutritional supports for patients is their obligations", and patients believe that "accepting nutritional supports is the responsibility of being a good patient". In addition, a Taiwanese tradition of "not becoming a starving soul after death and affecting one's later generations" often leads to families requiring that ANH be administered by the medical professionals [7]. When this happens, the medical professionals almost always cooperate with the request.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, no evidence that suggested that aggressive nutrition therapy can improve the quality of life. Chiu's study showed that ANH has no significant influence on survival [7]. However, an increasing number of literature reviews have suggested that ANH is a futile treatment and even brings more harm than good to terminal cancer patients, such as inducing anasarca or pulmonary edema [4,6,18,20,23,25].…”
Section: Introductionmentioning
confidence: 98%
“…Although parenteral nutrition/ hydration had few benefits for terminal patients, 27 inaccurate beliefs still existed among terminal patients and their families in Taiwan. 28,29 The use of parenteral nutrition/hydration requires rigorous guidelines. 30 The role of antibiotics in terminal cancer patients is interesting.…”
Section: Discussionmentioning
confidence: 99%